PLANNING TRAINING SESSIONS AIMED AT DEVELOPING PHYSICAL FITNESS IN 12–13-YEAR-OLD BASKETBALL PLAYERS - Ravshanova Izzat Inom qizi (International Journal of Literature and Language Studies, 2026)
This article discusses the scientific and methodological foundations of planning training sessions aimed at developing physical fitness in 12–13-year-old basketball players. This age period is considered an important stage in the physical, functional, and psychological development of young athletes. Therefore, special attention should be paid to the gradual development of speed, agility, coordination, explosive strength, flexibility, endurance, and movement accuracy during the training process. The article provides methodological recommendations on the proper distribution of training volume and intensity, the integration of technical and tactical preparation with physical exercises, the use of control tests, and the consideration of recovery processes. The content of the study is based on the analysis of scientific literature, modern approaches to the training of young athletes, and the principles of planning basketball training sessions.